PERSEPSI MASYARAKAT PETANI TERHADAP TRADISI RAMBU SOLO/PEMAKAMAN ADAT DI DESA MARINDING KECAMATAN MENGKENDEK KABUPATEN TANA TORAJA - Pebriani Soulun Salu; Charles R. Ngangi; Mex Frans Lodwyk Sondakh (Sam Ratulangi University, 2018)
This study aims to find out how the perceptions of the peasant community towards the tradition of rambu solo / traditional funeral in Marinding Village. This study lasted for 4 (four) months starting from April 2018 to July 2018 in Marinding Village, Mengkendek Sub-district, Tana Toraja Regency. The data collection method used is primary data collected through direct interviews with the community members and secondary data obtained from the Marinding Village Office. The sampling method used the purposive sampling method. The number of respondents is 15 people. Data analysis used was descriptive analysis. The results showed that there were two types of perceptions from the farmers community towards the tradition of rambu solo / traditional funeral in Marinding Village, Mengkendek Sub-district, Tana Toraja District, namely not supporting and supporting. There are 8 out of 15 respondents who do not support the rambu solo tradition because it is considered a waste that costs very large and expensive and is often for showing their social status in the community. But there is also support in which 7 out of 15 respondents support this tradition because the tradition of the rambu solo tradition reflects the life of the Toraja people who like togetherness and family. In addition, the implementation of solo signs opened up markets and huge profits for the rice farmers, coffee, and cattleman, especially for buffalos and pigs, because they could sell their all agricultural products to people who carried out rambu solo tradition which were usually carried out after the harvest period.*eprm*.